Hemodialysis catheter-related infection caused by Pannonibacter phragmitetus: a rare case report in China - Tang, Ruizhi; Wang, Jing; Zhan, Yu; Wu, Kaifu; Wang, Hui; Lu, Zhongxin (Frontiers in Cellular and Infection Microbiology, 2022)
Pannonibacter phragmitetus (P. phragmitetus) is rarely related with human disease. We reported a case of catheter-related infection caused by P. phragmitetus in a 68-year-old woman on hemodialysis. The patient developed recurrent fever during hemodialysis and blood cultures were positive for P. phragmitetus. The patient’s body temperature returned to normal after intravenous cefoperazone/sulbactam treatment, and the hemodialysis catheter was locked with gentamicin and urokinase. The potential anti-infective treatment against P. phragmitetus was discussed.